Antitussive codeine medicines in Ukraine: clinical and pharmacological, marketing, regulatory aspects, and forecasts - Nevzghoda, Oleksandr; Osyntseva, Alina; Shapovalov, Valentyn; Shapovalova, Viktoriia; Veits, Oleksandr (Annals of Mechnikov’s Institute, 2025)
Introduction. The circulation and use of codeine-containing medicines require careful regulation to ensure effective treatment of pain and cough and minimize the risks of misuse. In Ukraine, the availability of such medicines is the subject of regulatory measures aimed at maintaining a balance between accessibility and safety. This study examines the effectiveness, variety of dosage forms and regulatory aspects of codeine medicines in accordance with international standards. Materials and methods. The study was conducted on the basis of a systematic review of scientific literature and regulatory documents on the circulation and use of codeine medicines in Ukraine. The data analysis included a study of dosage forms, prescription rules and restrictions aimed at preventing abuse. Results. The study revealed a significant variety of dosage forms of codeine-containing medicines, with combined forms demonstrating advantages in the treatment of pain and cough. It was found that strict regulatory measures are in place, including mandatory registration, prescription-only dispensing and expiration date restrictions. However, gaps remain in awareness of the risks of misuse and the need for enhanced patient-physician collaboration. Conclusions. The analysis highlights the importance of optimizing the circulation and use of codeine-containing medicines to balance availability and safety. Improved control mechanisms and educational initiatives are essential to reduce the risks of misuse while ensuring effective patient treatment. Keywords: cough, codeine, codeines medicines, pharmacology, marketing, pharmacotherapy, regulatory barriers, safety